Evaluating the Healing Effects of Ajuga chamaecistus ssp. tomentella, on Second Grade Burn Wounds, a Double-Blind Randomized Controlled Clinical Trial - Aysan Rahiminiya; Mohammad Hossein Ayati; Laila Shirbeigi; Seyed Hamid Salehi; Seyyed Mohammad Bagher Fazljou; Seyede Nargess Sadati Lamardi; Hamideh Herizchi Ghadim* (Iranian Society of Pharmacognosy, 2022)
Background and objectives: Nowadays, the use of medicinal plants is on the rise mainly due to the fewer side effects and lower costs. Despite the traditional reports about the healing properties of Ajuga species, no clinical studies have been conducted. In this study, the effect of hydroalcoholic extract cream (3%) of Ajuga chamaecistus ssp. tomentella, one of the exclusive species of Ajuga in Iran, was compared with nitrofurazone cream (0.2%) on the second-degree burn wound healing. Methods: This clinical trial was performed at Motahhari Burns Hospital in Tehran. Fifty-two cases of second-degree burn patients were randomly assigned to two groups of 26 members, including nitrofurazone and Ajuga. We evaluated the wounds based on the onset of epithelialization, healing time, post-drug irritation, primary irritation, decreased irritation, post-drug pain, primary pain, decreased pain, allergy, infection parameters, and the Bates-Jensen Wound Assessment Tool. Results: Ajuga cream was more effective than nitrofurazone in terms of the mean day of epithelialization onset (p = 0.007), healing time (p = 0.001), post-drug irritation (p = 0.007), decreased irritation (p <0.001), post-drug pain (p = 0.018) and decreased pain (p = 0.001). Conclusion: According to the results, the Ajuga cream (3%) can be a useful remedy for burn wounds due to the reduction in the onset of epithelialization, healing time, post-drug irritation, irritation reduction, post-drug pain, and pain reduction. However, further large clinical trials are needed to confirm these results.